Utilization of long-lasting insecticide-treated net and its associated factors among pregnant women in Dawo district, Southwest Shoa Zone, Oromia, Ethiopia, 2023 - Negasa, Kumsa; Huluka, Tufa Kolola; Yebassa, Mecha Aboma; Waqkene, Tolossa (Frontiers in Public Health, 2024)
Introduction The use of long-lasting insecticide-treated net (LLIN) is one of the most effective malaria prevention strategies, particularly among pregnant women. It has mosquito-killing repellent and physical barrier properties. Pregnant women, children under 5 years of age, and patients with HIV/AIDS, as well as non-immune migrants, mobile populations, and travelers, are the most vulnerable groups to malaria. Even when pregnant women are given priority, not all nets owned by households are used by pregnant women. Therefore, the risk of the occurrence of malaria during pregnancy is also high. Objective This study aimed to assess the utilization of long-lasting insecticide-treated net and its associated factors among pregnant women in Dawo district, Southwest Shoa Zone, Oromia, Ethiopia, 2023. Methods A community-based analytical cross-sectional study was carried out in Dawo district, Southwest Shoa Zone, Oromia, Ethiopia, from 21 to 30 April 2023. A total of 353 pregnant women were chosen through simple random sampling and interviewed face-to-face using a structured and pre-tested questionnaire. Before being exported to the Statistical Package for Social Science (SPSS) version 23, the data were coded and entered into EPIDATA version 4.6. The study examined the prevalence of long-lasting insecticide-treated net use among pregnant women in the Dawo district using descriptive statistics. Analytical statistics, such as bivariable and multivariable logistic regression analyses, were used to determine the relationship between independent and dependent variables. Statistical significance was determined using a P-value of <0.05 and adjusted odd ratios with 95% confidence intervals. Results Long-lasting insecticide-treated nets were utilized by 55.5% (95% CI: 50.4–60.7%) of all pregnant participants in the study, which was below the national target. Pregnant women who have antenatal care (ANC) contact for current pregnancy adjusted odds ratio (AOR = 4.66, 95% CI: 1.95, 11.10), community-based health insurance (CBHI) enrollment (AOR = 2.38, 95% confidence intervals, CI: 1.38, 4.11), children under 5 years of age (AOR = 2.68, 95% CI: 1.62, 4.43), understanding that malaria poses a risk to fetuses (AOR = 3.25, 95% CI: 1.26, 8.41), and LLINs access (AOR = 12.47, 95% CI: 3.98, 39.08), were factors that significantly associated with LLIN utilization. Conclusion In conclusion, the utilization of LLINs was relatively low. ANC contact for current pregnancy, CBHI enrollment, having children under the age of 5, having a high income, and understanding that malaria poses a risk to fetuses were factors significantly associated with LLIN utilization among pregnant women.